Catalytic mechanism and activity of N2 reduction on boron-decorated crystalline carbon nitride. (1st October 2022) - Zheng, Mei; Cai, Xu; Li, Yi; Ding, Kaining; Zhang, Yongfan; Chen, Wenkai; Sun, Chenghua; Lin, Wei
Abstract: The development of efficient, low-cost, and eco-friendly catalysts for nitrogen fixation is essential and provides an alternative method to the traditional Haber–Bosch process. However, studies on thermal catalyst of nitrogen fixation mainly focus on metal-containing, and the microscopic mechanism of thermal reduction process is still limited. Herein, we explored an economic metal-free boron atom decorated poly(triazine imide) (B/PTI), a crystalline carbon nitride, as an excellent thermal catalyst of nitrogen fixation and proposed a substrate-hydrogen mechanism for the N2 thermal reduction reaction (NTRR). Our results reveal that the substrate hydrogen as the hydrogen source can promote the hydrogenation process with activation barrier of 0.56 eV, significantly lower than that of reported NTRR catalysts. Importantly, the B/PTI exhibits high turnover frequency, which is comparable to Fe, Ru, and Ti catalysts. Our work offers new insights into NTRR mechanism and provides an alternative solution for the sustainable ammonia synthesis.